Bone Mineral Density in Stroke Patients - Nilüfer Balcı; Nehir Samancı; Ümit Dündar; Akın Yıldız; Mehmet Arman (Galenos Yayinevi, 2005)
Objective: Fractures after stroke are usually caused by the development of hemiosteoporosis and the high incidence of falls. The aim of this study was to compare bone mineral densities (BMDs) of paretic and nonparetic limbs in stroke patients and to investigate factors determining this difference. Patients and Medhods: Twenty-nine stroke patients with a mean duration of illness 14.34 ± 15.65 months were included in the study. BMDs were measured with dual-energy x-ray absorptiometry (DEXA) from distal radius and femoral neck bilaterally. Activities of daily living and spasticity were also evaluated. Results: Mean age of the patient population was 58.29 ± 12.42 years. 15 patients were within the first year of the stroke, while 14 had a history more than 1 year. Femoral neck BMD were significantly lower in the paretic side; however there was no significant difference for distal radius BMDs. BMD of the affected femoral neck correlated negatively with age, duration of stroke and years since menopause and positively with body weight, FIM scores and spasticity. In addition, there was a positive correlation between all BMDs and FIM scores. At regression analysis, degree of bone loss in femoral neck of paralysed side depended on duration of stroke, age and FIM scores. Conclusion: In conclusion, BMD was decreased significantly in the lower limb of paretic side in stroke patients. This decrease might be prevented or reduced by early rehabilitation.